2021
DOI: 10.3390/ijerph18126616
|View full text |Cite
|
Sign up to set email alerts
|

A Threat of Customer Incivility and Job Stress to Hotel Employee Retention: Do Supervisor and Co-Worker Supports Reduce Turnover Rates?

Abstract: The study investigates the impact of customer incivility, job stress, perceived supervisor support, and perceived co-worker support on the turnover intention of frontline employees. A survey-questionnaire approach was used to collect the point of view of frontline employees that work in five-star hotels in a metropolitan city of Korea. Four independent variables that were extracted from valid theoretical backgrounds along with four demographic variables were used in the study. The regression analysis was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 86 publications
(180 reference statements)
0
16
0
1
Order By: Relevance
“…Customer misbehaviour stood out as a key impact of the pandemic for employees with the vast majority of our respondents reporting that they have experienced and/or witnessed abuse and/or harassment from customers. Few hospitality studies consider customer abuse across a diverse set of hospitality workplaces with extant research on the impact of COVID-19 focussing on occupational stress and coping rather than customer mistreatment (Lippert et al , 2021) or on customer mistreatment experienced by specific groups such as café workers (Ahmed et al , 2021), hotel workers (Chung et al , 2021) or immigrant hospitality workers (Sönmez et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Customer misbehaviour stood out as a key impact of the pandemic for employees with the vast majority of our respondents reporting that they have experienced and/or witnessed abuse and/or harassment from customers. Few hospitality studies consider customer abuse across a diverse set of hospitality workplaces with extant research on the impact of COVID-19 focussing on occupational stress and coping rather than customer mistreatment (Lippert et al , 2021) or on customer mistreatment experienced by specific groups such as café workers (Ahmed et al , 2021), hotel workers (Chung et al , 2021) or immigrant hospitality workers (Sönmez et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings contribute to the understanding of customer incivility in the new service marketplace. Although an increasing body of research has revealed that customer incivility is detrimental to FSEs’ work outcomes during the pandemic (Ahmed et al , 2022; Chung et al , 2021; Yue et al , 2021), whether this detrimental effect has aggravated since the outbreak of the pandemic remains unknown. The change in the magnitude of the negative effect of customer incivility on FSEs can be only captured by comparing pre- and postpandemic samples.…”
Section: Discussionmentioning
confidence: 99%
“…Of many work stressors, customer incivility (i.e. rude or insulting behavior perpetrated by customers) has been identified as a key stressor to FSEs (Ahmed et al , 2022; Chung et al , 2021; Yue et al , 2021). While recent studies have shown that customer incivility has an adverse effect on FSEs’ well-being and work outcomes (Ahmed et al , 2022; Chung et al , 2021; Yue et al , 2021), whether this negative effect of customer incivility has exacerbated under an imminent environmental crisis remains unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its pervasiveness in all environments is reflected in the research literature that documents the problem in both the private and public sectors (Catley et al, 2013; Hutchinson & Jackson, 2015; Nguyen et al, 2019). Workplace bullying is known to occur in offices and manufacturing factories (Rodriguez, 2017; Salin, 2001; Sims & Sun, 2012), in corporate boardrooms (Harvey et al, 2006), in tax-funded community services (Gershman, 2014; Griffith et al, 2016; Kim et al, 2018), in health care venues (Hutchinson et al, 2006; Lamberth, 2015; Shabazz et al, 2016 ), in service industries providing social support and assistance (Hallberg & Strandmark, 2006; Inness et al, 2008), and in the hospitality industry (Chung et al, 2021; Okafor & Okoye, 2017; Ram, 2015) There are many examples of workplace bullying in institutions of higher education (Hodgins et al, 2017; Hollis, 2015; Howard, 2011; Zabrodska & Kveton, 2013), in politics and all levels of government (Francis, 2019; Reid, 2009, 2016; Rheault et al, 2019), as well as in religious institutions (Finlan, 2015; Turner, 2018). With no workplace assured of protection from bullying, it is not surprising that individuals at any level of an organization can become unwilling targets of abuse, or bystanders who witness attacks against colleagues.…”
mentioning
confidence: 99%